Causal effects between gut microbiota and endometriosis: a two-sample Mendelian randomisation study - Tiefeng Cao; Yunfei Wang; Shen Huimin (Journal of Obstetrics and Gynaecology)
Background Previous observational evidence has indicated the potential involvement of the gut microbiota (GM) in the development of endometriosis. However, the causal relationship of the association remains to be investigated.Method Genome-wide association study (GWAS) data of GM was obtained from the MiBioGen consortium, and GWAS for endometriosis data was from the FinnGen consortium. Initially, a two-sample Mendelian randomisation (MR) analysis was performed to identify specific bacteria associated with endometriosis. Inverse variance-weighted (IVW) was used as the main MR analysis to infer causal relationships. The other four popular MR methods including MR-Egger regression, weighted mode, weighted median, and simple mode were used for secondary confirmation. Subsequently, these selected bacteria were employed as exposure to investigate their causal effects on six sub-types of endometriosis. Furthermore, reverse MR analysis was implemented to evaluate the reverse causal effects. Cochran’s Q statistics was used to test the heterogeneity of instrumental variables (IVs); MR-Egger regression was used to test horizontal pleiotropy; MR-PRESSO and leave-one-out sensitivity analysis were applied to find significant outliers.Result A total of 1131 single nucleotide polymorphisms (SNPs) were collected as IVs for 196 GM taxa with endometriosis as the outcome. We identified 12 causal relationships between endometriosis and GM taxa including 1 phylum, 3 families, 2 orders, and 6 genera (Rikenellaceae RC9 gut group, Eubacterium ruminantium group, Faecalibacterium, Peptococcus, Clostridium sensu stricto 1, and Ruminococcaceae UCG005). Utilizing the Bonferroni method, we identified phylum Cyanobacteria as the strongest associated GM taxa. Subsequently, 6 significant causal effects were uncovered between the 12 selected specific GM and 6 sub-types of endometriosis. Meanwhile, no reverse causal relationship was found. Further, no horizontal pleiotropy and no significant outliers were detected in the sensitive analysis.Conclusions This MR analysis revealed significant causal effects between GM and endometriosis and phylum Cyanobacteria had the strongest association.